Answer:
b. if dont d cuz I did this one but I kinda forgot
Answer:
The original equation must have been:
![7x^{2} -5x-2=0](https://tex.z-dn.net/?f=7x%5E%7B2%7D%20-5x-2%3D0)
Step-by-step explanation:
A quadratic equation is in the form of :
![ax^{2} +bx+c=0](https://tex.z-dn.net/?f=ax%5E%7B2%7D%20%2Bbx%2Bc%3D0)
And it is solved in the form of :
and
Now the given equation is :
![x=\frac{-(-5)+-\sqrt{(-5)^{2} -4(7)(-2)} }{2(7)}](https://tex.z-dn.net/?f=x%3D%5Cfrac%7B-%28-5%29%2B-%5Csqrt%7B%28-5%29%5E%7B2%7D%20-4%287%29%28-2%29%7D%20%7D%7B2%287%29%7D)
We can see that here;
a = 7
b = -5
c = -2
So, the original equation must have been:
![7x^{2} -5x-2=0](https://tex.z-dn.net/?f=7x%5E%7B2%7D%20-5x-2%3D0)
About 20 times to be almost accurate check my math plz.
WELCOME!
Answer:
x² + 10x + 25
Explanation:
Before we begin, remember the following:
(a + b)(a + b) = (a + b)² = a² + 2ab + b²
Now, for the given we have:
(x + 5)(x + 5)
We can note that the two brackets are identical.
Therefore, we can apply the above rule as follows:
(x + 5)(x + 5) = (x + 5)²
= (x)² + 2(x)(5) + (5)²
= x² + 10x + 25
Hope this helps :)
Answer:
![\huge \boxed{K=20}\checkmark](https://tex.z-dn.net/?f=%5Chuge%20%5Cboxed%7BK%3D20%7D%5Ccheckmark)
B. 20
Step-by-step explanation:
<em>First, you divide by 5 from both sides of equation.</em>
<em>
</em>
<em>Simplify, to find the answer.</em>
<em>
</em>
<em>
, which is our answer.</em>